Efficacy of Periconceptional High-Dose Folic Acid in Isolated Orofacial Cleft Prevention: A Systematic Review - Jayarajan, Rajshree; Natarajan, Anantharajan; Nagamuttu, Ravindranathan (Indian Journal of Plastic Surgery, 2019)
Background The effectiveness of folic acid in prevention of neural tube defects has been well established. Periconceptional supplementation of folic acid in low doses has been shown to be effective in some studies on its efficacy in prevention of occurrence of clefts. There are few studies on high-dose folic acid for prevention of occurrence and recurrence of clefts in high risk cases and the overall consensus based on these is not available.Objectives The aim of this review is to assess whether high-dose folic acid supplementation during the periconceptional period reduces the risk of occurrence of nonsyndromic clefts and recurrence in high-risk cases.Search Methods Search was conducted in the various databases and trial registers. There were no restrictions in the search with regards to language, study setting, or date of publication.Results The search yielded four studies—one randomized control trial, two prospective control trials, and a case–control surveillance on screening 401 articles. The three case–control studies were specifically on recurrence of clefts in high risk cases. The heterogeneity of the studies prevented conduction of a meta-analysis. But results of the studies demonstrate a strong association between high-dose folic acid and isolated nonsyndromic cleft lip with or without cleft palate (CL±CP). But such an effect is weak with regards to isolated cleft palate (CP).Conclusions With the limited evidence available, our conclusion is that high-dose folic acid probably has a role in prevention of recurrence of isolated CL±CP in high-risk individuals, but not CP.
Keywords: periconception; high-dose folic acid; cleft lip; cleft palate